Millennial’s Leadership Development: A Systematic Literature Review - Irwan Dewanto; Donald Crestofel Lantu; Achmad Fajar Hendarman; Agung Wicaksono (Journal of Educational, Health and Community Psychology, 2022)
This study explores existing research and papers on the millennial leadership concept and finds a research gap in the millennial leadership development concept. This research analyzes emerging topics linked to the current study development issue in reaching the recent study's movement. This research aims to recognize the present study and the research gap in millennial leadership development. Recent research implicates whether workforce leadership development research has been conducted from the leadership perspective. In addition, this study explores the gaps in the current research, such as a lack of reflection on millennials' leadership development. The result confirms that there has not been depth research on millennials' leadership development. Besides, there is a robust suggestion that a mixed-method research approach from emerging and developing countries with various learning style perspectives has not been considered extensively in this field of study.